The race towards a New York convention for cross-border mediated settlement agreements: The fable of the tortoise and the hare revisited? - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2014)
In this post on the Kluwer Mediation Blog, some thoughts on the discussions on the New York Convention for Mediation are presented.